Group Investigation Flipped Learning in Achieving of Students’ Critical and Creative Thinking Viewed from Their Cognitive Engagement in Learning Physics - Tegeh, I Made; Santyasa, I Wayan; Agustini, Ketut; Santyadiputra, Gede Saindra; Juniantari, Made (Universitas Pendidikan Ganesha, 2022)
In 21st century, students in schools especially in learning physics must be facilitated with student centered learning models that are integrated with technology, such as group investigation flipped learning (GrIFL) as instead of direct flipped learning (DFL) model. This study aims to analyze the main and interactive effects between the GrIFL model and the DFL model on students' critical and creative thinking viewed from their cognitive ingagement in learning physics. To achieve this goal, experimental research was conducted using a post test only control group design. The sample was selected by class random technique. The research data were collected by critical thinking tests, creative thinking tests, and cognitive engagement questionnaires. The research data were analyzed using two-way multivariate analysis of variance. The results showed that the critical thinking and creative thinking of students who studied with the GrIFL model were higher than students who studied with the DFL model; students who had high cognitive engagement showed the same critical thinking skills as those who had low cognitive involvement, but creative thinking of students who have high cognitive involvement is higher than students who have low cognitive involvement; there is no interactive effect between learning models and students' cognitive ingagement on critical thinking and creative thinking. The implication of this research is that in order to achieve optimal critical thinking and creative thinking, physics learning will be better if using the GrIFL model.